2017
DOI: 10.1155/2017/7952782
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Chloride Smoke Inhalation Induced Severe Acute Respiratory Distress Syndrome: First Survival in the United States with Extended Duration (Five Weeks) Therapy with High Dose Corticosteroids in Combination with Lung Protective Ventilation

Abstract: Zinc chloride smoke bomb exposure is frequently seen in military drills, combat exercises, metal industry works, and disaster simulations. Smoke exposure presents with variety of pulmonary damage based on the intensity of the exposure. Smoke induced severe acute respiratory distress syndrome (ARDS) is often fatal and there are no standard treatment guidelines. We report the first survival of smoke induced severe ARDS in the United States (US) with prolonged use of high dose steroids (five weeks) and lung prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Also, the 2006 ARDS Network Trial (26) found worse outcomes when steroids were started late in the disease course, and no change in outcomes when they were started earlier (despite short term improvements in physiologic measures of ventilation and perfusion). On the other hand, the use of steroids has been associated with survival in elderly patients in one registry based review (27) as well as dramatic clinical improvement on VA-ECLS in a number of case reports (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the 2006 ARDS Network Trial (26) found worse outcomes when steroids were started late in the disease course, and no change in outcomes when they were started earlier (despite short term improvements in physiologic measures of ventilation and perfusion). On the other hand, the use of steroids has been associated with survival in elderly patients in one registry based review (27) as well as dramatic clinical improvement on VA-ECLS in a number of case reports (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Also, pirfenidone has been suggested and tried successfully in the treatment of ARDS due to white smoke-induced ARDS [11]. As another example, Zinc Chloride smoke (white smoke) inhalation induced severe ARDS has been successfully treated with a combination of pirfenidone and corticosteroids [35,64].…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…The produced smoke (ZnCl 2 smoke) mainly contains zinc chloride (ZnCl 2 ), zinc oxide, and other chemical ingredients. Inhalation of the high doses of ZnCl 2 smoke would likely cause acute lung injury (ALI), even then develop acute respiratory distress syndrome (ARDS) (Mahboob et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%